Keadilan Organisasional, Trust, dan Komitmen Organisasional Berpengaruh Terhadap Organizational Citizenship Behavior pada Karyawan PT Boga Inti [Organizational Justice, Trust and Organizational Commitment Affecting Organizational Citizenship Behavior of Employees of PT Boga Inti] - Harianto, Teh; Meilani, Yohana F. Cahya Palupi (Universitas Pelita Harapan, 2023)
Based on interviews with the Operational Director, Human Capital and Legal Director and Finance and Accounting Director, confirmation of several issues related to organizational citizenship behavior (OCB) was obtained. In conditions of limited manpower planning, everyone is required to work more than usual, whether it's within the scope of his own work, or also work in other units. Incomplete involvement and participation of all employees, especially for programs carried out by different departments. This causes the programs or policies implemented are not optimal. There is still a lack of employee involvement and participation, especially programs related to different divisions. This study uses multiple linear regression. Involvement of organizational commitment, organizational justice and trust as factors that influence the OCB. The results show that the three factors above play an important role in realizing OCB which will have positive benefits for achieving the company's vision and mission. Bahasa Indonesia Abstrak: Berdasarkan wawancara dengan Operational Director, Human Capital and Legal Director dan Finance and Accounting Director, didapatkan konfirmasi beberapa issue yang berkaitan dengan organizational citizenship behavior (OCB) ini. Dalam kondisi manpower planning yang terbatas, setiap orang diperlukan untuk bekerja lebih dari biasanya, apakah itu di dalam cakupan pekerjaan dia sendiri, atau juga pekerjaan di unit lain. Keterlibatan dan partisipasi seluruh karyawan yang tidak sepenuhnya, terutama untuk program yang dilakukan oleh departemen berbeda. Hal ini menyebabkan program atau kebijakan yang dilakukan tidak maksimal. Keterlibatan dan partisipasi karyawan masih kurang, terutama program yang berkenaan dengan divisi yang berbeda. Penelitian ini menggunakan multiple linear regression, dengan rumus Slovin. Keterlibatan komitmen organisasi, keadilan organisasi dan trust sebagai faktor yang memengaruhi OCB tersebut. Hasilnya terlihat bahwa ketiga faktor di atas memegang peranan penting dalam terwujudnya OCB yang akan bermanfaat positif bagi tercapainya visi dan misi perusahaan.